Solution of the First-Passage Problem by Advanced Monte Carlo Simulation Technique - Labou, M. (Проблемы прочности, 2003)
A selective Monte Carlo simulation procedure
for the evaluation of the reliability of nonlinear
structures subjected to dynamic loading is presented.
The proposed “Russian Roulette and
Splitting” procedure allows generation of important
low-probability samples in nonlinear dynamics.
This procedure is quite efficient in
comparison to the straightforward Monte Carlo
simulation method and allows evaluation of the
nonlinear stochastic response in a very low
probability domain. Предложен модифицированный численный метод Монте-Карло для оценки надежности
нелинейных конструкций, подвергнутых динамическому нагружению. Использование метода
позволяет обобщить важные низковероятностные выборки для нелинейных динамических
задач. Эффективность данного метода по сравнению с прямом методом Монте-Карло
состоит в возможности определения нелинейного стохастического отклика в области
очень низких вероятностей. Запропоновано модифікований числовий метод Монте-Карло для оцінки
надійності нелінійних конструкцій під дією динамічного навантаження.
Метод дозволяє узагальнити важливі низькоімовірнісні вибірки для нелінійних
динамічних задач. Ефективність даного методу в порівнянні з прямим
методом Монте-Карло полягає в можливості визначення нелінійного сто-
хастичного відгуку в області дуже низьких імовірностей.